High-resolution computed tomography as a non-invasive imaging biomarker for interstitial lung diseases: a tertiary center study - Senger, Krishna Pratap Singh; Singh, Ankita (International Journal of Advances in Medicine, 2021)
Background: Interstitial lung diseases (ILD) are a heterogeneous group of non-neoplastic disorders resulting from damage to the lung parenchyma by varying patterns of inflammation and fibrosis. With high-resolution computed tomography (HRCT) the pattern of lung damage can be mapped accurately which may help to identify specific ILD. Methods: 65 diagnosed cases of ILD by HRCT who were admitted to a tertiary care chest hospital, formed the study group. All these patients also underwent histopathological confirmation as per hospital protocol. The study was done over a period from August 2016 to July 2019. Clinical details, chest x-ray, HRCT and histopathological data was collected and analysed using 2x2 table for detecting sensitivity, specificity, positive predictive value (PPV) and negative predictive values (NPV). Results: For diagnosing ILD like acute interstitial pneumonia (AIP), LIP and RB ILD the HRCT fared equally well in diagnostic utility as compared to histopathological examination. But in certain conditions like non-specific interstitial pneumonia (NSIP) the HRCT performed poorly in terms of PPV as compared to gold standard histopathology. In Bronchiolitis obliterans organizing pneumonia (BOOP) and usual interstitial pneumonia (UIP) again the HRCT performed fairly well as compared to gold standard. Conclusions: HRCT shows good correlation with histopathological diagnosis in identifying a various subtype of ILD and may thus serve a useful non-invasive, imaging biomarker not only for diagnosing a particular ILD but for prognostication and response to treatment.